Effects of Substitution Position of Carbazole-Dibenzofuran Based High Triplet Energy Hosts to Device Stability of Blue Phosphorescent Organic Light-Emitting Diodes - Kyung Hyun Choi; Jae Min Kim; Won Jae Chung; Jun Yeob Lee (Molecules, 2021)
High triplet energy hosts were developed through the modification of the substitution position of carbazole units. Two carbazole-dibenzofuran-derived compounds, 9,9′-(dibenzo[b,d]furan-2,6-diyl)bis(9H-carbazole) (26CzDBF) and 4,6-di(9H-carbazol-9-yl)dibenzo[b,d]furan (46CzDBF), were synthesized for achieving high triplet energy hosts. In comparison with the reported hole transport type host, 2,8-di(9H-carbazol-9-yl)dibenzo[b,d]furan (28CzDBF), 26CzDBF and 46CzDBF maintained high triplet energy over 2.95 eV. The device performances of the hosts were evaluated with electron transport type host, 2-phenyl-4, 6-bis(3-(triphenylsilyl)phenyl)-1,3,5-triazine (mSiTrz), to comprise a mixed host system. The deep blue phosphorescent device of 26CzDBF:mSiTrz with [[5-(1,1-dimethylethyl)-3-phenyl-1H-imidazo[4,5-b]pyrazin-1-yl-2(3H)-ylidene]-1,2-phenylene]bis[[6-(1,1-dimethylethyl)-3-phenyl-1H-imidazo[4,5-b]pyrazin-1-yl-2(3H)-ylidene]-1,2-phenylene]iridium (Ir(cb)3) dopant exhibited high external quantum efficiency of 22.9% with a color coordinate of (0.14, 0.16) and device lifetime of 1400 h at 100 cd m−2. The device lifetime was extended by 75% compared to the device lifetime of 28CzDBF:mSiTrz (800 h). These results demonstrated that the asymmetric and symmetric substitution of carbazole can make differences in the device performance of the carbazole- and dibenzofuran- derived hosts.